Implementation of a modified carrier-based PWM technique for a cascaded MLI using DSP microcontroller - Youssef Babkrani; Gourmaj mourad; Ahmed Naddami; Karim Choukri; Sanaa Hayani Mounir (Institute of Advanced Engineering and Science, 2023)
A multi-level converter is a power electronic device desired to generate a desired AC voltage level using several introduced DC voltages, the output voltage of the converter is characterized by a low harmonic content (THD) compared to conventional inverters. The adopted innovative design permits the independent control of PV modules, enabling, in this way, to operate independently and won’t be very affected by intermittence. Additionally in this paper, a new control strategy based on sinusoidal pulse width modulation (SPWM) technique is analyzed for cascaded H-Bridge inverter. In this new technique, separate modified carriers are used for each H-Bridge (HB). Multiple-carrier SPWM is used with the new control SPWM technique. Those carriers are being implemented with diverse sinusoidal dispositions phase disposition (PD), phase opposition and disposition (POD), alternative opposition and disposition (APOD), and with altered frequencies. Experimental results are obtained while using different operating conditions.